Spontaneous antiferromagnetic order and strain effect on electronic properties of α-graphyne. (May 2018) - Dong, Baojuan; Guo, Huaihong; Liu, Zhiyong; Yang, Teng; Tao, Peng; Tang, Sufang; Saito, Riichiro; Zhang, Zhidong
Abstract: Using hybrid exchange-correlation functional in ab initio density functional theory calculations, we study magnetic properties and strain effect on the electronic properties of α-graphyne monolayer. We find that a spontaneous antiferromagnetic (AF) ordering occurs with energy band gap (∼0.5 eV) in the equilibrated α-graphyne. Bi-axial tensile strain enhances the stability of AF state as well as the staggered spin moment and value of the energy gap. The antiferromagnetic semiconductor phase is quite robust against moderate carrier filling with threshold carrier density up to 1.7 × 10 14 electrons/cm 2 to destabilize the phase. The spontaneous AF ordering and strain effect in α-graphyne can be well described by the framework of the Hubbard model. Our study shows that it is essential to consider the electronic correlation effect properly in α-graphyne and may pave an avenue for exploring magnetic ordering in other carbon allotropes with mixed hybridization of s and p orbitals. Graphical abstract: Image 1